Kepatuhan Wajib Pajak Orang Pribadi: Peran Sosialisasi, Moral Pajak, dan PPS - Afifa Rizky Putri; Kurnia Kurnia (Universitas Muhammadiyah Metro, 2025)
One of the main sources of government revenue is taxes, which are a way for people to contribute to development. Studying the impact of tax morale, tax socialization, and voluntary disclosure by the North Makassar Tax Service Office (KPP) regarding taxpayer compliance is the main objective of this research. North Makassar KPP Pratama taxpayers are the target of this inspection. Questionnaires were distributed to obtain quantitative primary data. The sample consists of 100 participants selected through convenience sampling. Data analysis included the use of the R-squared value, F test, and multiple linear regression. The findings demonstrate that tax education, tax ethics, and voluntary disclosure initiatives at North Makassar KPP Pratama have a positive impact on taxpayer adherence.